Świat dziecka w wybranych wierszach Joanny Kulmowej - Rogalska, Elżbieta (Kultura-Społeczeństwo-Edukacja, 2020)
“Children’s need for miracles” has been accentuated as elements appearing in the selected poems by Joanna Kulmowa, which allow the child to be amazed by the world; they are a predicator to the appearance of tutoring. The astonishment with the world, as a place full of lyricism, enables the consolidation of identity by the emergence of the child’s “I”. Not judging and classifying. Subjectivity is emphasized: the seriousness of the child’s world, understanding oneself, transforming the world, individuality, respect, acceptance, cooperation, responsibility, independence, sense of agency and dialogue. It was concluded that the main “miracle” is dialogue which: requires presence to be astonished by the world; raises the child’s responsibility for another person; cannot be deprived of love; manifests itself in the “question-cry “ for presence as a result of trust in the subject of the relationship. The objectives of the study were: to define dialogue as Bettelheim’s “miracle” in selected poems by J. Kulmowa; demonstrate that selected poems of J. Kulmowa are dialogical. The aim of the article was to: present the “miracles” in the child’s world in selected poems by Joanna Kulmowa. The method of hermeneutics was used based on the methodology of Wolfgang Klafka. It seems important that so far the selected poetry of J. Kulmowa has not been interpreted in relation to Bettelheim’s concept of “miracle” and its connection with the philosophy of dialogue, pedagogy and literary studies at the same time.